Psychological profiles of effeminate, male and female students - Noor, Noraini M.; Abd Rahman, Shukran; Farooqui, Jamil; Nasr, Ahmad Muhammad; Md. Noon, Hazizan (Psychologia Society, Kyoto University, 2003)
This study examined the psychological profile of effeminates (n = 45) in comparison with matched-groups of normal males (n = 45) and females (n=45). Respondents were Malaysian students aged between 19-24 years. Results of the one-way analyses of variance showed that effeminate students were similar to females in terms of their perceptions of their body image, thinking, and gender characteristics. However, they were more androgynous than normal female students. Although effeminates reported the lowest level of self-esteem, contrary to prediction, they showed low psychological distress. The results are discussed with respect to their current situation as well as the general literature in this area.